Preparation method and application of monodisperse heteropolyacid-based Pt atomic catalyst constructed based on double confinement strategy
By adopting a double-limited domain strategy in Pt-POM composite materials, Pt atoms are anchored at the quadruple hollow sites of Keggin-type POM and isolated with porous carbon, the problems of active site aggregation and poor conductivity are solved, and efficient hydrogen transport channels and stable catalysts are achieved.
Patent Information
- Application Number
- CN202411714728.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-11-27
AI Technical Summary
The existing Pt-POM composites have problems of active site aggregation and poor conductivity, which limits their application in the field of electrochemistry.
The double-limited domain strategy is adopted to anchor the active metal Pt atoms at the quadruple hollow site of the Keggin-type POM, and the POM is isolated using porous carbon to achieve the double-limited domain effect.
An efficient hydrogen transport channel was constructed, which significantly promoted the progress of hydrogen precipitation reaction (HER) and improved the stability and conductivity of the catalyst.
Smart Images

Figure CN119824463A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of functional materials, and specifically relates to a preparation method and application of a monodisperse heteropolyacid-based Pt atom catalyst constructed based on a double confinement strategy. Background Art
[0002] Hydrogen evolution by water electrolysis has attracted extensive attention as an effective way to generate and store clean energy using renewable energy. Among them, Pt-based catalysts are considered to be the most efficient catalyst type in the hydrogen evolution reaction (HER) under alkaline conditions. Due to the high cost and scarcity of metal Pt, a large number of researchers have increased the dispersion of Pt on the support by shrinking the metal Pt to the atomic scale. The formation of atomically dispersed metal Pt (Pt SAs) is mainly through the anchoring of adjacent strongly electronegative atoms (O / N / S) to form HER active sites (Pt-O / Pt-N / Pt-S). In the catalytic system, Pt SAs catalysts have attracted much attention due to their unique geometric and electronic properties, the highest atomic utilization efficiency and uniform active sites. However, highly dispersed metal atoms may move and agglomerate due to high surface energy, resulting in poor stability; or they may be fixed due to excessive interaction with the support, resulting in passivation of active sites.
[0003] In recent years, researchers have developed a variety of Pt single-atom catalysts to solve this problem. One important strategy is to combine Pt with heteropolyacids (POMs). Heteropolyacids have excellent electron transport capabilities, and their surfaces are rich in O active sites, especially the quadruple hollow sites, which show strong adsorption capacity for metal single atoms. Some studies have loaded heteropolyacids on commercial carbon materials and then loaded Pt. The results show that when the interaction between Pt and the heteropolyacid carrier is stronger than the cohesive energy of Pt atoms, Pt can remain atomically dispersed; otherwise, aggregation occurs. Based on this, scholars further studied the confinement of heteropolyacids and chloroplatinic acid in the MOF framework, forming a structure in which Pt atoms are dispersed on the quadruple hollow sites of phosphomolybdic acid confined by MOF. However, high-energy electron beams easily destroy the MOF structure, resulting in the inability to accurately locate metal atoms. In addition, MOF materials have poor stability and conductivity, which limits their application in the field of electrochemistry. Therefore, developing an efficient and stable Pt single atom-POM catalyst, especially for industrial electrocatalytic applications, has become a key issue that needs to be solved urgently. Summary of the invention
[0004] The present invention aims at the problems of active site aggregation and poor conductivity in the existing Pt-POM composite materials, provides a preparation method and application of a monodisperse heteropolyacid-based Pt atomic catalyst constructed based on a double confinement strategy, and constructs a general strategy for stabilizing double confinement atomic-level dispersed catalysts. The so-called double confinement refers to anchoring the active metal Pt atoms in the quadruple hollow sites (4-H sites) of the Keggin-type POM, and isolating the POM using porous carbon (PC) with a suitable pore size, thereby achieving a double confinement effect. The unique oxygen sites of POMs can effectively capture Pt single atoms through the metal-O four-coordination structure and improve proton transport. At the same time, the multi-shell structure of POM (such as Pt-O-Mo-O...) can provide abundant hydrogen transfer sites for the anchored metal atoms. PC can not only significantly improve the conductivity of the material, but also stabilize the structure of POM through the confinement effect. Therefore, by confining Pt atoms on POM clusters and using PC with sub-nanometer pores for secondary confinement, an efficient hydrogen transmission channel can be constructed, which significantly promotes the hydrogen evolution reaction (HER).
[0005] The present invention adopts the following technical solution: The difficulty of confinement lies in accurately placing a single Pt atom on an isolated heteropoly acid and requiring a simple system to anchor the single Pt atom. Therefore, the present invention anticipates the use of a "two-step method" to first precisely confine the heteropoly acid in a microporous carbon substrate with a pore size that matches its size. This not only stabilizes the confined guest molecules, but also further optimizes the electronic state of the active center of the heteropoly acid. Subsequently, thanks to the quadruple hollow sites of the Keggin-type heteropoly acid for the precise anchoring of the Pt atom, the goal of dispersing a single Pt atom on each heteropoly acid is achieved by controlling the Pt precursor content. In this way, through layer-by-layer confinement, a supported single-atom catalyst with unique structural and electronic properties can be obtained.
[0006] The specific steps are as follows: S1. Preparation of unimodal ultraporous carbon PC: The main micropore size of sucrose-derived carbon is about 0.75~2 nm, which is close to the size of Keggin-type heteropolyacid anions. Therefore, sucrose was selected as the precursor to prepare ultraporous carbon by a typical carbonization activation method. Sucrose was mixed with sodium bicarbonate in a mass ratio of 4 / 1 and ground thoroughly in an agate mortar. Subsequently, the mixture was heated to 400 ℃ and 900 ℃ in an argon atmosphere in a tube furnace at a heating rate of 10 ℃ / min for 1 h each. The obtained product was stirred in a hydrochloric acid aqueous solution (v / v=1:1), the solution was filtered and dried at 70 ℃ to obtain unimodal ultraporous carbon PC; S2, single confined material PMo 12 Preparation of PC: 25 mg PC was mixed with 10 mL 0.01 M phosphomolybdic acid (PMo 12) aqueous solution, stirred for 3 h, and then filtered to recover the corresponding solid product. Subsequently, the sample was filtered and washed until the pH value of the filtrate reached 7.0, and dried overnight to obtain the single confined material PMo 12 @PC.
[0007] S3, double confinement material Pt 1 @PMo 12 Preparation of @PC: PMo 12 The @PC (25 mg) sample was dispersed in 10 mL of ultrapure water and then magnetically stirred for 20 min to obtain a uniform suspension. Next, 260 μL of H 2 PtCl 6 6H 2 O aqueous solution (20 mg / mL). After stirring at 60 °C for 16 h, the suspension was separated by centrifugation. The precipitate was washed several times with ultrapure water and then dried under vacuum at 60 °C overnight. As a control, pure PC and commercial activated carbon (AC) supported PMo 12 Also used to support Pt, denoted as Pt 1 @PC and Pt-PMo 12 / AC.
[0008] The beneficial effects of the present invention are as follows: The present invention proposes a dual confinement strategy to construct an efficient and stable Pt single atom-POM catalyst. The isolated Pt atoms are confined in PMo 12 In the PMo 12 The resulting Pt 1 The @POMs@PC series of catalysts have excellent HER activity and stability. This design can build an efficient hydrogen transmission channel and significantly promote the hydrogen evolution reaction (HER). Thanks to the dual confinement design, the catalyst and stability are also significantly improved, providing a new way for efficient energy conversion. BRIEF DESCRIPTION OF THE DRAWINGS
[0009] Figure 1 TEM image of precursor PC; Figure 2 For the precursor PMo 12 @TEM image of PC; Figure 3 Pt 1 @PMo 12 @TEM image of PC; Figure 4 Pt 1 @PMo 12 HAADF-STEM image of @PC; Figure 5 Pt 1 @TEM image of PC; Figure 6 Pt 1 -PMo 12 TEM image of @AC; Figure 7 0.5 MH 2 SO 4 Medium PMo 12 @PC,Pt 1 @PC,Pt 1 @PMo 12 HER polarization curves and corresponding Tafel plots of @PC and 20% Pt / C; Figure 8 This is a chronopotentiometry test under acidic conditions. DETAILED DESCRIPTION
[0010] The present invention is further described with reference to examples.
[0011] 1. Double confined atomically dispersed catalyst (Pt 1 @PMo 12 Preparation of @PC (1) Preparation of unimodal ultraporous carbon (PC): The main micropore size of sucrose-derived carbon is about 0.75~2 nm, which is close to the size of Keggin-type heteropolyacid anions. Therefore, sucrose was selected as the precursor to prepare ultraporous carbon by a typical carbonization activation method. Sucrose and sodium bicarbonate were mixed in a mass ratio of 4 / 1 and ground thoroughly in an agate mortar. Subsequently, the mixture was heated to 400 ℃ and 900 ℃ in an argon atmosphere in a tube furnace at a heating rate of 10 ℃ / min for 1 h each. The obtained product was stirred in a hydrochloric acid aqueous solution (v / v=1:1), the solution was filtered and dried at 70 ℃. Figure 1 It can be seen that the TEM image of PC mainly shows a thin silk-like structure with a large number of micropores on the surface, which is conducive to the PMo 12 The limited domain.
[0012] (2) Single confined material (PMo 12 Preparation of PC: 25 mg PC and 10 mL PMo 12 (0.01 M) aqueous solution, stirred for 3 h, and filtered to recover the corresponding solid product. Subsequently, the sample was filtered and washed until the pH value of the filtrate reached 7.0, and dried overnight. Figure 3 It can be seen that the load PMo 12 After that, the TEM image also retains the silk-like amorphous structure of PC. 12No micropores and nanoparticles or clusters were observed in @PC, which may be due to the uniform dispersion of smaller phosphomolybdic acid.
[0013] (3) Double confinement materials (Pt 1 @PMo 12 Preparation of @PC Then PMo 12 The @PC (25 mg) sample was dispersed in 10 mL of ultrapure water and then magnetically stirred for 20 min to obtain a uniform suspension. Next, 260 μL of H 2 PtCl 6 6H 2 O aqueous solution (20 mg / mL). After stirring at 60 °C for 16 h, the suspension was separated by centrifugation. The precipitate was washed several times with ultrapure water and then dried under vacuum at 60 °C overnight. As a control, pure PC and commercial activated carbon (AC) supported PMo 12 Also used to support Pt, denoted as Pt 1 @PC and Pt-PMo 12 / AC. From Figure 3 Pt shown in 1 @PMo 12 @PC TEM shows that there are still no particles and the carbon skeleton remains intact, which proves that Pt and PMo 12 monodisperse state. Figure 4 The spherical aberration electron microscopy image further observed that isolated and uniformly distributed clusters (75-0.8 nm) were loaded on the PC of the double confined material, and each bright Pt site was located at the corresponding PMo 12 These demonstrate the successful synthesis of dual-confined materials. Figure 5 It can be seen that Pt 1 @PC also maintains the silk-like structure of PC, indicating the atomic distribution of Pt. However, it should be noted that the random distribution of Pt anchors on PC is random and the binding may be unstable. Figure 6 It can be seen that in Pt-PMo 12 @AC formed larger nanoparticles, indicating that the confined PMo 12 It plays a very important role in the secondary confinement of Pt atoms.
[0014] 2. HER electrochemical performance test under alkaline conditions The performance of electrochemical hydrogen evolution reaction (HER) was tested on a conventional three-electrode system of a CHI 760E electrochemical workstation. A catalyst-covered L-shaped glassy carbon electrode (3 mm in diameter) was used as the working electrode, saturated calomel (SCE) was used as the reference electrode, and a graphite rod was used as the counter electrode. All polarization curves were corrected with 90% iR compensation to eliminate the ohmic drop on the electrolyte. 2 mg of catalyst powder and 5 μL of Nafion (20 wt%) were dispersed in 550 μL of deionized water and 180 μL of isopropanol and sonicated for 1 h to form a uniform catalyst ink. 3.5 μL of the well-dispersed catalyst ink was dropped onto a pre-polished glassy carbon electrode (0.07 cm 2 ) and dried at room temperature for measurement. The catalyst was tested by linear sweep voltammetry (LSV), Tafel slope and electrochemical impedance spectroscopy (EIS) using an electrochemical workstation to evaluate its electrocatalytic performance.
[0015] First, the reference electrode was calibrated with a reversible hydrogen electrode (RHE) in high-purity H 2 Saturated 0.5 MH 2 SO 4 In the solution, two Pt foils were used as the working electrode and the counter electrode, respectively, and saturated calomel was used as the reference electrode. The potential range was -0.2 to -0.4 V at 2 mV s -1 Cyclic voltammetry (CV) was performed at a scan rate of 1.5 MH / s, and the average of the two potentials with zero current was taken as the thermodynamic potential of the hydrogen electrode reaction. 2 SO 4 The CV results for the RHE calibration of mercury / mercuric oxide can be described as E ( vs. RHE) = E ( vs. Saturated calomel) +0.2636 V.
[0016] The three-electrode system was then placed at 0.5 MH 2 SO 4 LSV experiments were performed in the solution with potentials ranging from -0.15 to -0.42 V and -0.85 to -1.2 V, respectively, and a scan rate of 5 mV s -1 , the Tafel slope is determined by plotting the current density versus the logarithm of the overpotential (log |j|).
[0017] The EIS performance was measured in the frequency range of 0.01 Hz to 100 kHz. The CP experiment was performed at 0.0007 A (i.e. 10 mAcm -2 The solution resistance R can be obtained through the impedance spectrum. s, then use E = E RHE - 90%iR s To correct the LSV curve for liquid resistance. vs. The impedance test is carried out under RHE potential. The solution resistance R can be obtained through the impedance spectrum. s , then use E = E RHE - 90%iR s To perform liquid resistance correction on the LSV curve.
[0018] 3. Electrocatalytic hydrogen evolution test: First, the synthesized Pt 1 @PMo 12 The @PC catalyst was uniformly coated on the platinum carbon electrode to prepare a working electrode for electrochemical testing. The hydrogen evolution reaction (HER) activity of the sample under alkaline conditions was then measured using an electrochemical workstation in a three-electrode system. LSV, EIS and CV tests were performed in sequence according to the same electrochemical test method as step 2. According to the method shown in step 2, the R s The LSV curve is corrected for liquid resistance.
[0019] By performing multiple impedance tests on the samples, it can be obtained that the average solution resistance of the catalyst in the acidic electrolyte is 7.5 Ω, and the LSV curve is corrected for liquid resistance based on this result.
[0020] Figure 7 Pt 1 @PMo 12 @PC, precursor and comparison system were tested for electrochemical performance. The results showed that under acidic conditions, Pt 1 @POMs@PC has the lowest overpotential and the lowest Tafel slope. This shows that the confined PMo 12 The presence of PMo can build an efficient hydrogen transport channel and significantly promote the hydrogen evolution reaction (HER). 12 The rich oxygen on the Pt atoms can increase the high coverage of H* on the Pt atoms, provide a rich local H-rich microenvironment for the Pt atoms, and promote the HER reaction.
[0021] from Figure 8 It can be seen that Pt 1 @PMo 12 The @PC catalyst exhibited high catalytic HER durability and showed no obvious attenuation after a long period of 100 h, which was due to the stable reaction environment provided by the dual confinement strategy.
[0022] Based on the above test results, it can be seen that the double-confined atomic-level Pt 1 @PMo12 @PC catalyst exhibits excellent electrocatalytic HER activity and stability under acidic conditions. 12 It provides a rich local H-rich microenvironment for Pt atoms and constructs an efficient hydrogen transport channel, which effectively improves the rate of hydrogen evolution reaction. 1 @PMo 12 @PC catalyst provides an effective way to improve the efficiency of electrocatalytic HER and has potential application prospects.
[0023] In view of the problems of active site aggregation and poor conductivity in existing Pt-POM composite materials, the present invention proposes a general strategy for constructing a stable dual-confined atomic-level dispersed catalyst. The so-called dual confinement refers to anchoring the active metal Pt atoms in the quadruple hollow sites (4-H sites) of Keggin-type POM, and isolating the POM by porous carbon (PC) with a suitable pore size, thereby achieving a double confinement effect. Compared with the existing technology, the unique oxygen sites of POMs can effectively capture Pt single atoms through the metal-O four-coordination structure and improve proton transport. At the same time, the multi-shell structure of POM (such as Pt-O-Mo-O...) can provide abundant hydrogen transfer sites for the anchored metal atoms. PC can not only significantly improve the conductivity of the material, but also stabilize the structure of POM through the confinement effect. Therefore, by confining Pt atoms on POM clusters and using PC with sub-nanometer pores for secondary confinement, an efficient hydrogen transfer channel can be constructed, which significantly promotes the hydrogen evolution reaction (HER). This innovative design provides a new direction for the development of efficient electrocatalysts in the future.
[0024] The above-mentioned implementation mode is only used to illustrate the content of the present invention, but it is not a limitation of the present invention. Relevant technical personnel in this field can also make corresponding adjustments and modifications without departing from the scope of the present invention. Therefore, all technical solutions formed by equivalent replacement or equivalent modification belong to the protection scope of the present invention.
Claims
1. A method for preparing a monodisperse heteropolyacid-based Pt atom catalyst based on a dual confinement strategy, characterized in that: The so-called double confinement refers to anchoring the active metal Pt atoms in the quadruple hollow sites of the Keggin-type POM, while using porous carbon PC with appropriate pore size to isolate the POM, thereby achieving a double confinement effect.
2. The method for preparing a monodisperse heteropolyacid-based Pt atom catalyst based on a dual confinement strategy according to claim 1, characterized in that: The steps include: S1. Preparation of unimodal ultra-microporous carbon PC: Sucrose and sodium bicarbonate were mixed and ground thoroughly in an agate mortar. Subsequently, the mixture was heated to 400 °C and 900 °C for 1 h each at a heating rate of 10 °C / min in a tube furnace under an argon atmosphere. The obtained product was stirred in a hydrochloric acid aqueous solution with a volume ratio of 1:1, the solution was filtered and dried at 70 °C to obtain unimodal ultra-microporous carbon PC; S2, single confined material PMo 12 Preparation of @PC: PC was mixed with phosphomolybdic acid aqueous solution, stirred for 3 h, and then filtered to recover the corresponding solid product. Subsequently, the sample was filtered and washed until the pH value of the filtrate reached 7.0, and dried overnight to obtain the single confined material PMo 12 @PC; S3, double confinement material Pt1@PMo 12 Preparation of @PC: PMo 12 The @PC sample was dispersed in ultrapure water and then magnetically stirred for 20 min to obtain a uniform suspension. Then, H2PtCl6·6H2O aqueous solution was slowly added and stirred at 60 °C for 16 h. The suspension was centrifuged and the separated precipitate was washed several times with ultrapure water and then dried under vacuum at 60 °C overnight to obtain Pt1@PMo. 12 @PC.
3. The method for preparing a monodisperse heteropolyacid-based Pt atom catalyst based on a dual confinement strategy according to claim 2, characterized in that: In S1, the mass ratio of sucrose to sodium bicarbonate is 4:
1.
4. The method for preparing a monodisperse heteropolyacid-based Pt atom catalyst based on a dual confinement strategy according to claim 2, characterized in that: In S2, the usage ratio of PC and phosphomolybdic acid is 25 mg:10 mL, wherein the concentration of phosphomolybdic acid is 0.01 M.
5. The method for preparing a monodisperse heteropolyacid-based Pt atom catalyst based on a dual confinement strategy according to claim 2, characterized in that: In S3, PMo 12 The usage ratio of @PC, ultrapure water, and H2PtCl6·6H2O aqueous solution is 25 mg:10 mL:260 μL, wherein the concentration of H2PtCl6·6H2O aqueous solution is 20 mg / mL.
6. A monodisperse heteropolyacid-based Pt atom catalyst constructed based on a double confinement strategy prepared by the preparation method as claimed in claim 1 for use in hydrogen evolution reaction.
Citation Information
Patent Citations
Preparation method of palladium or platinum and heteropolyacid co-loaded nano porous carbon composite material
CN112169841A
Non-noble metal cathode hydrogen evolution catalyst for PEM electrolyzed water and application of non-noble metal cathode hydrogen evolution catalyst
CN117802526A